EXPLORING PERCEPTION OF BULLYING AT THE WORKPLACE: A CASE STUDY OF SOCSO SUNGEI PETANI, KEDAH - Khalidass, Thivya; Mariamdaran Chethiyar, Saralah Devi (SARJANA, 2022)
Bullying is becoming increasingly common in our society today despite being a deviant behavior and also a criminal offense. This problem occurs among employees both in public and private sectors. This study as such aims to discuss the perception of workplace bullying among employees of Social Security Organization (PERKESO) located in Sungai Petani, Kedah. Low awareness among employees concerning bullying is yet to raise the alarm on the seriousness of the problem in our community. This quantitative study is conducted to explore the perception on bullying comprising 45 employees from the organization using a simple random sampling method. Research data was obtained through the distribution of a set of questionnaires. The instrument used in this study is the Revised Malaysian Bullying Questionnaire (R-MBQ). The perceptions of the employees are studied through various types of bullying behavior such as bullying in the form of personal attacks and contempt with several demographic variables. The results of the study reveals that there is no much differences in the perception on bullying among employees based on those demographic variables.